ANALYSIS OF DESCRIPTIVE ITEM TEST FOR THE MID-TERM EVEN SEMESTER SUMMATIVE OF THE MERDEKA CURRICULUM FOR EIGHT-GRADERS SCIENCE SUBJECT AT SMP NEGERI 20 LEBONG ACADEMIC YEAR 2024/2025 - Asmi Astuti; Dharmawati Ambarita; Jeli Dahliah; M. Thoha; Kashardi; Merri Sri Hartati; Reny Dwi Riastuti (International Journal of Teaching and Learning, 2025)
This study aims to analyse the quality of the descriptive items used in the mid-semester summative assessment (even semester) of the Ilmu Pengetahuan Alam (Science) subject for eighth-grade students at SMP Negeri 20 Lebong in the 2024/2025 academic year. This analysis is important to ensure that the test items used in the learning evaluation not only align with the learning objectives but also effectively assess students' critical thinking skills, conceptual understanding, and scientific abilities. The research employed a descriptive quantitative design with an evaluative approach. Data were obtained through documentation of descriptive items and students’ answer sheets, which were then analysed using test item quality indicators, including content validity, reliability, difficulty level, and discriminating power. Data were collected through a descriptive test consisting of 10 items. The data source consisted of 37 answer sheets from eighth-grade students of SMP Negeri 20 Lebong. The findings indicate that six descriptive questions (60%) are valid, while four questions (40%) are invalid. The descriptive questions are categorised at an adequate level of dependency with a consistency score of 0.443. The results of very good, good, quite good, and bad are indicated by the discrimination power of descriptive questions. There are three different categories for the level of difficulty of descriptive questions: moderate, easy, and too easy. The study suggests that “very good” questions could be reused, while “bad or invalid” questions could be revised from scratch based on their indicators. On the other hand, most of the students' learning outcomes meet the KKTP or the Learning Target Achievement Criteria.